Sustainable development, climate change vulnerability, governance and oil rent: the case of Saudi Arabia/ Zuhayr Khan Mustun - Mustun, Zuhayr Khan (Universiti Teknologi MARA Selangor, 2022)
This empirical investigation has aimed at exploring the impact of climate change vulnerability, governance, and oil rent on sustainable development in Saudi Arabia, for the period 1998 to 2019. The econometric analysis uses OLS regressions, and various findings have emerged. Climate change vulnerability positively influences sustainable development, which can be attributed to the continuous adaptation and mitigation efforts to tackle the country's harrowing effects of climate change. Likewise, oil rents report a favourable impact on sustainable development, implying the Kingdom’s efforts to balance the adverse consequences of fossil fuel dependency on environmental quality. In contrast, the governance score is negative; hence, the composite effect on sustainable development is nefarious, although the result is statistically not significant. Furthermore, health expenditure per capita positively influences sustainable development, but the result is statistically insignificant. Moreover, the analyses also show tgrowth development, proxied by GDP, has been negatively impacting sustainable development. Lastly, FDI is found to be harmful to sustainable development in the case of Saudi Arabia. The study recommends ongoing investments towards climate change policymaking and development, and triggers strident calls for economic diversification of moving assets towards “greener” sectors. Similarly, the health care sector requires a revamp in quality and delivery s to contribute more effectively towards sustainable development. Most importantly, the governance structure and quality of institutions in Saudi Arabia require a profound transformation, so that good governance and efficient public administration become key players in the advancement of the Saudi Vision 2030 agenda, otherwise, the ambitions of the Kingdom might reach to a standstill.